How emotions work - "Katz, Jack" (Chicago, 1999)
How can it be that rational adults suddenly find themselves making obscene gestures at drivers who just cut them off? Why do people react with tears to events as disparate as winning a sports championship and the death of a parent? How can a child cry continuously in a cunningly strategic manner for five minutes, and then speak with no trace of the tears that were just shed? Jack Katz develops methods for unravelling these mysteries. His book undertakes to answer the fundamental questions at the heart of our emotional life. Katz fills the book with real-life emotions - crying under the pressure of police interrogation, road rage on California freeways, laughter in a funhouse, 8-year-olds shamefacedly striking out at baseball games - where their rise and fall can be observed without the artificial influence of the research process. By using videotapes, interviews, ethnographic description, participant observation and the insights of novelists, Katz studies emotions as physical and embodied - vibrantly, "under the radar" of a person's perceptual reach - rather than as remembered and recounted. Katz illustrates his methods with photographs and video stills that demonstrate the embodiment of emotion. The portrait that emerges is one in which people are much more sensually, intimately and aesthetically bound up in the landscapes of their lives than previous scientific studies would suggest. The text seeks to reveal the poetic and coherent logic of emotional experience and revolutionize the study of this enigmatic and essential aspect of human life.
Keywords: Emotions-Social aspects